Pemetaan Distribusi Curah Hujan Rata-Rata Menggunakan Metode Isohyet di Wilayah Kabupaten Tangerang - Lutfiah Nurhijriah; Yayat Ruhiyat; asep saefullah; Diana Ayu Rostikawati (Newton-Maxwell Journal of Physics, 2022)
The purpose of this study was to obtain information related to the distribution mapping of average rainfall in the Tangerang Regency area. Hydrological analysis is needed in determining the average rainfall in an area, one of which is by using the Isohyet method. The isohyet method is a method of making a connecting line that brings together points of the same rain depth. The research was conducted by analyzing rainfall data in the Tangerang Regency area in the last five years, namely the period 2016 to 2020. The research data were obtained from three observation stations, namely: 1. Budiarto Curug Meteorological Station, 2. Pondok Betung Climatology Station, and 3. Ciputat Region II BMKG Station.  This research was conducted in two activities, namely: 1. Rainfall data collection, and 2. Data processing using Minitab and ArcGIS applications. Based on the results of processing rainfall data for the 2016-2020 period at three observation stations, the P-Value was 0.115 and the Kolmogorof Smirnov test value was 0.103 for heading 1, P-Value was 0.115 and the Kolmogorof Smirnov test value was 0.103 for heading 2, and P-Value < 0.010 and the Kolmogorof-Smirnov test value of 0.195 for heading 3. The results of the calculation of rainfall from the three observation posts show that the rainfall in the Tangerang Regency area is normally distributed. The results of the rainfall mapping using the Isohyet method also show that the rainfall in the Tangerang Regency area is evenly distributed.